Analisis Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Pemoderasi - Widiawati, Hestin Sri; Linawati, Linawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of the establishment of a company is none other than to get high profits, this can be achieved if the company can make high sales as well. For this reason, companies are required to be able to attract investors to invest their capital. Company value greatly influences the decision of prospective investors to invest their capital. The purpose of this study was to determine the effect of profitability and leverage on firm value with CSR as a moderating variable. The population of this research is companies registered in the Bursa Efek Indonesia (BEI) in 2015-2019. The research sample selection uses purposive sampling which is tested by using moderating regression analysis. Based on the results of testing the hypothesis in this study shows that the profitability proxied by ROA partially has a significant effect on firm value, with a significant value of t test of 0.031. Leverage proxied by DER partially has a significant effect on firm value, with a t test significance value of 0.012. CSR disclosure is not able to moderate the relationship between profitability and corporate value, with a significant value of t test of 0.082. CSR disclosure is able to moderate the relationship between leverage and firm value, with a t-test significance value of 0,000. And simultaneously Profitability, Leverage, CSR moderation on Profitability, and CSR moderation on Leverage have a significant effect on Company Value, with a significant value of f test of 0,000.